Navigating Worlds in an Ecumenical Journey: Philip A. Potter (1921-2015) - A Tribute with a Difference - Jagessar, Michael N. (Black theology, 2015)
Philip A. Potter was one of the giants of the ecumenical movement in the middle to latter half of the last century. A Caribbean Methodist, Potter was a gregarious polymath, whose interests spanned Biblical studies, systematic theology, inter faith relations, and, of course, ecumenism. Potter died a few months ago and although advanced plans were already in place for this issue of the journal in terms of the agreed content, we felt it would be remiss of us if space were not found to mark the death of this great man. This essay is a slightly adapted essay that was previous published in a reader dedicated to marking the life and indefatigable work of Philip A. Potter.